A Pilot Trial of a Computerized Renal Template Note to Improve Resident Knowledge and Documentation of Kidney Disease - Shirazian, S; Wang, R.; Moledina, D.; Liberman, V.; Zeidan, J.; Strand, D.; Mattana, J. (Applied Clinical Informatics, 2013)
Background: Kidney disease is under-documented in physician notes. The use of template-guided notes may improve physician recognition of kidney disease early in training.Objective: The objective of this study was to determine whether a computerized inpatient renal template note with clinical decision support improves resident knowledge and documentation of kidney disease.Methods: In this prospective study, first year medical residents were encouraged to use the renal template note for documentation over a one-month period. The renal template note included an option for classification of acute kidney injury (AKI) and chronic kidney disease (CKD) categories with a link to standard classifications. Pre- and post-knowledge of AKI and CKD categories was tested with a quiz and surveys of resident experience with the intervention were conducted. Appropriate AKI and/or CKD classification was determined in 100 renal template notes and 112 comparable historical internal medicine resident progress notes from approximately one year prior.Results: 2,435 inpatient encounters amongst 15 residents who participated were documented using the renal template note. A significantly higher percent of residents correctly staged earlier stage CKD (CKD3) using the renal template note compared to historical notes (9/46 vs. 0/33, p<0.01). Documentation of AKI and more advanced CKD stages (CKD4 and 5) did not improve. Knowledge based on quiz scores increased modestly but was not significant. The renal template note was well received by residents and was perceived as helping improve knowledge and documentation of kidney disease.Conclusions: The renal template note significantly improved staging of earlier stage CKD (CKD3) with a modest but non-significant improvement in resident knowledge. Given the importance of early recognition and treatment of CKD, future studies should focus on teaching early recognition using template notes with supplemental educational interventions.Citation: Shirazian S, Wang R, Moledina D, Liberman V, Zeidan J, Strand D, Mattana J. A pilot trial of a computerized renal template note to improve resident knowledge and documentation of kidney disease. Appl Clin Inf 2013; 4: 528–540http://dx.doi.org/10.4338/ACI-2013-07-RA-0048
Keywords: Clinical decision support systems; kidney disease; medical education; electronic medical records; templates